From Traditional Practices to Modern Interventions: Exploring Herbs Role in Treating Liver Cancer Following Its Signalling Pathways (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
The foremost hepatocellular carcinoma is a primary reason for cancer-causing death globally. It ranks as the second main factor in male cancer-related mortality and the fourth nearly prevalent neoplasm overall. Compared to women, men are more likely to acquire hepatoma. Many risk factors have been related to liver cancer which include Cirrhosis, NAFLD, NASH, viral hepatitis, Intake of Alcohol, Aflatoxins, Obesity & Diabetes, Iron overload, Tobacco use, Exposure to certain chemicals, Family history, etc. Any chronic inflammatory liver disease can cause HCC, but cirrhosis is the pathophysiological process that is present in cases of the disease. There are several treatments approaches available for hepatocellular carcinoma (HCC), including surgery, immunotherapy, liver transplantation, and chemotherapy. However, these treatments have not significantly improved outcomes for HCC patients. An herbal medicine containing natural compounds has become a viable therapeutic choice for various diseases, including cancer. Among these, some herbal components are interested in treating HCC. All these below-mentioned plants have anticancer properties. They work against cancer cells through various pathways and are responsible for apoptosis, Antiproliferation, cytotoxicity, etc. All this study has been conducted on multiple cell lines in vitro studies. Herbal medicine is often more affordable and accessible than conventional cancer treatments, particularly in regions where access to healthcare is limited. Growing attention has been shown in researching and developing herbal medication used to treat cancer, leading to the discovery of new compounds and formulations with potential therapeutic benefits. In this aspect, we are highlighting various expected pathways to cure HCC.